2016
DOI: 10.3126/ijls.v10i1.14512
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Some Physiological Traits in Spring Safflower (Carthamus tinctorius L.) Cultivars under Water Stress

Abstract: This research was conducted in 2013 to investigate changes in some physiological traits of spring safflower cultivars (C1; Faraman, C2; Goldasht; C3; Sina and C4; Soffeh) under different irrigation treatments (I1, I2, I3, I4 for irrigation after 70, 100, 130 and 160 mm evaporation from class A pan, respectively). The experiment was arranged as split plot based on randomized complete block design in three replicates. Relative water content (RWC), membrane stability index (MSI) and total chlorophyll decreased, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Safflower is an essential oilseed crop that can moderately tolerate against several environmental stresses including drought (Mohammadi et al, 2016 management practices affected the oil content of safflower cultivars. Among the environmental stresses, water deficient condition increase protein and decrease oil contents of safflower (Nabipour et al, 2007;Amini et al, 2014).…”
Section: Safflower (Carthamus Tinctorius L)mentioning
confidence: 99%
“…Safflower is an essential oilseed crop that can moderately tolerate against several environmental stresses including drought (Mohammadi et al, 2016 management practices affected the oil content of safflower cultivars. Among the environmental stresses, water deficient condition increase protein and decrease oil contents of safflower (Nabipour et al, 2007;Amini et al, 2014).…”
Section: Safflower (Carthamus Tinctorius L)mentioning
confidence: 99%
“…Furthermore, tolerant plants accumulate soluble compatible substances including proline and soluble sugars without hampering enzyme activities which, thereby, decreases the water potential [ 15 ]. Thus, tolerant plants modulate the adverse effects of drought stress through photosynthetic adjustment, osmolytes accumulation, and activities of genes that encode antioxidant enzymes [ 16 ]. Under drought stress, plants hamper transpiration phenomenon through different mechanisms such as closing the stomata, and developing stomatal resistance parallel with decreasing stomatal conductivity [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in line with Kassahun et al (2010) , who demonstrated that delayed leaf senescence often confers tolerance to post flowering moisture stress in sorghum. RWC is often used as a screening tool for drought tolerance, as water content and water potential are considered physiologically appropriate indicators of drought effects ( Mohammadi et al, 2016 ). Tolerant genotypes often maintain higher values of RWC in stress, as evident in the present study by genotypes A1 (92.3 ± 2.13), EC-523368-2 (87.3 ± 2.52), Bhima (86.5 ± 2.99) and GMU 2347 (84.7 ± 1.46).…”
Section: Discussionmentioning
confidence: 99%